Information seeking by participants enrolled in randomized clinical trials of behavioral interventions - Kathryn M. Ross; Kelsey M. Arroyo; Megan A. McVay (Contemporary Clinical Trials Communications, 2025)
Background: Little is known regarding information seeking by participants in randomized clinical trials (RCTs) of behavioral interventions. The current study explored the prevalence of information seeking, whether information seeking varied by participant demographic characteristics, and whether information seeking affected participants' study knowledge or trial-related behavior. Methods: Adults who were currently or recently enrolled in a behavioral RCT completed an online survey. Respondents were asked retrospectively about their trial participation history, information seeking behavior before and after trial enrollment, and how any information found impacted their trial experience. Results: Respondents (N = 92) predominantly identified as women (70.7 %) and White (62.0 %), had an average (mean ± SD) age of 45.1 ± 12.4 years, and were enrolled in trials with a range of foci, from weight loss (38 %) to smoking cessation (31.5 %) and mental health (22.8 %). Overall, 37 % searched for trial information at least once, with 28.3 % searching before enrollment and 17.4 % after enrollment, most commonly via internet search engines. Participants searched for details regarding trial length, study conditions, expected findings, and compensation. Searching for information was not associated with experience during trial consent. Searching prior to enrollment generally increased likelihood of enrollment, whereas searching after enrollment was reported to have limited to no effect on trial behavior. Discussion: A sizable minority of trial participants search for trial information from outside sources, which may support increased enrollment. Investigators should consider how information shared online (e.g., via protocol papers or ClinicalTrials.gov) describes study hypotheses and intervention techniques to avoid potential bias due to participant demand characteristics or intervention diffusion.